2015
DOI: 10.1016/j.jeurceramsoc.2014.07.032
|View full text |Cite
|
Sign up to set email alerts
|

3D mapping of anisotropic ferroelectric/dielectric composites

Abstract: Macroscopic anisotropy in polycrystalline materials is of key interest since it may help filling the gap between randomly oriented polycrystals like ceramics and single crystals. Non-destructive X-ray Computed Micro Tomography (XCMT) is a necessary step towards the full control and modelling of such anisotropy, beyond the standard scheme of interfaces. To ascertain this progress, XCMT is applied to 3D mixtures of ferroelectric and dielectric oxides processed by Spark Plasma Sintering (SPS). In such conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This is both a confirmation of pre-existing phenomenological models and a first step towards a realistic modeling of such dielectric composites which usually require strong simplifying assumptions. 52 …”
Section: Multimaterials At the Microscalementioning
confidence: 99%
“…This is both a confirmation of pre-existing phenomenological models and a first step towards a realistic modeling of such dielectric composites which usually require strong simplifying assumptions. 52 …”
Section: Multimaterials At the Microscalementioning
confidence: 99%
“…It can be observed that in 2D approximation, εeff is underestimated by comparison with the 3D approach, but still it can be considered that a 2D simulation describes quite satisfactory the dependence of εeff on the dielectric component concentration as a trend. This difference concerning the estimation of εeffwas also presented by J. Lesseur et al in a very recent study . However, the dependences of the tunability on the dielectric phase concentration present significant differences in the two approaches.…”
mentioning
confidence: 99%
“…We will focus on the core-shell approaches dedicated to the composite route that is particularly suitable not only to tailor the dielectric characteristics but also to generate new functionalities [6][7][8][9]. The major issue when designing tailor-made nanostructured ferroelectric materials is the control of the interfaces in a broad sense i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Magnesium oxide was also widely used in ferroelectric/dielectric composites designed at the microand the nanoscale to decrease the dielectric losses while keeping moderate permittivity in the range 500-1000 [7,8,42]. Aiming once again a control of the dielectric phase at the grain scale, we successfully adapted an original method based on thermolysis process for an efficient coating on ferroelectric particles surface by a crystallized MgO shell [43].…”
Section: Magnesium Oxide Based Core-shell Nanocompositesmentioning
confidence: 99%